EFFECTIVE GOVERNANCE AND MANAGEMENT OF TERTIARY EDUCATION FOR SOCIO-ECONOMIC DEVELOPMENT IN NIGERIA - SHITTU, Afeez Adehsina; Adeseko Sunday OLAIFA; Amudalatu Abiodun SAGAYA; Abiodun Johnson MEDUPIN (Jurnal Saintifik (Multi Science Journal), 2025)
This paper discussed the inadequacy of effective governance and management in tertiary education institutions in West African countries, specifically focusing on Nigeria. It argued that while these institutions had produced programs to meet the labour market's needs, educational policies and curriculum reforms had not kept pace with economic and political development. This resulted in a brain drain as university professionals sought better opportunities elsewhere. The paper aimed to address the role of university stakeholders in Nigeria's social and economic development in line with sustainable development goals. The authors suggested that university elites and professionals should be allowed to participate in political and financial contributions towards national development without political affiliation or intimidation. This would improve and increase Nigeria's socio-economic development. The authors highlighted the importance of effective governance and management in tertiary education institutions, as seen in developed countries where they contributed significantly to socio-economic development. University professionals' current denial of political and economic contributions has hindered progress in Nigeria. In conclusion, the authors emphasised the need for a national policy that allowed professionals from tertiary institutions to participate in political and economic roles to contribute to the country's national development. This would improve Nigeria's socio-economic development and address the brain drain issue.